Role of G proteins and ERK activation in hemin-induced erythroid differentiation of K562 cells - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
Heterotrimeric G proteins which couple extracellular signals to intracellular effectors play a central role in cell growth and differentiation. The pluripotent erythroleukemic cell line K562 that acquires the capability to synthesize hemoglobin in response to a variety of agents can be used as a model system for erythroid differentiation. Using Western blot analysis and RT-PCR, we studied alterations in G protein expression accompanying hemin-induced differentiation of K562 cells. We demonstrated the presence of G(alpha s), G(alpha i2) and G(alpha q) and the absence of G(alpha i1), G(alpha o) and G(alpha 16) in K562 cells. We observed the short form of G alpha s to be expressed predominantly in these cells. Treatment of K562 cells with hemin resulted in an increase in the levels of G(alpha s) and G(alpha q). On the other hand, the level of G(alpha i2) was found to increase on the third day after induction with hemin, followed by a decrease to levels lower of those of uninduced cells, The mitogen-activated protein kinase ERK1/2 pathway is crucial in the control of cell proliferation and differentiation. Both G(i)- and G(q)-coupled receptors stimulate MAPK activation. We therefore examined the phosphorylation of ERK1/2 during hemin-induced differentiation of K562 cells. Using anti-ERK1/2 antibodies, we observed that ERK2 was primarily phospborylated in K562 cells. ERK2 phosphorylation increased gradually until 48 h and returned to basal values by 96 h following hemin treatment. Our results suggest that changes in G protein expression and ERK2 activity are involved in hemin-induced differentiation of K562 cells. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: erythroid differentiation; hemin; G proteins; ERK1/2 phosphorylation; K562; NUCLEOTIDE-BINDING-PROTEIN; HETEROTRIMERIC G-PROTEINS; ALPHA-SUBUNIT; MEGAKARYOCYTIC DIFFERENTIATION; ERYTHROLEUKEMIA-CELLS; 3T3-L1 CELLS; HEL CELLS; EXPRESSION; ACID; PATHWAYS